PROTOCOL FOR PLANTLET REGENERATION VIA ENHANCED SHOOT PROLIFERATION IN MURRAYA KOENIGII (L.) SPRENG. - NISHA KHATIK; RAMESH JOSHI (International Journal of Pharma and Bio Sciences, 2015)
An efficient protocol for high frequency regeneration of plantlets from epicotyl and cotyledonary node explants of an important medicinal plant Murraya koenigii was developed. Explants were obtained from 60 days old axenic seedlings of Murraya koenigii and cultured on Murashige and Skoog (MS) medium supplemented with plant growth regulators to ascertain the suitable explants and media composition for mass production. Multiple shoot induction was achieved on Murashige and Skoog (MS) basal medium augmented with different concentrations of 6-benzyleaminopurine (BAP) 2.78 to 17.38 µM, Kinetin (Kin.) 0.62 to 11.21 µM and Indole-3-acetic acid (IAA) 0.29 to 5.12 µM. Percentage response of epicotyl explants was 95.2±0.07 which was significantly higher than the response of cotyledonary node (89.4±0.34%) explant. The 40-45 mm elongated shoots were cultured to in MS basal medium augmented with different concentrations of indole-3-butyric acid (IBA). The maximum percentage, 93.4±2.30 of rooting was achieved on MS basal medium containing 9.98 µM IBA. The plantlets were hardened prior to field transfer. Ninety percent hardened plantlets were successfully survived under natural conditions.